2022
DOI: 10.21203/rs.3.rs-2166006/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased Interleukin-6 is Associated with Long COVID-19: Evidence from a Systematic Review and Meta-analysis

Abstract: Background: Coronavirus disease 2019 (COVID-19) can involve persistence, sequelae, and other clinical complications that last weeks to months to evolve into long COVID-19. Exploratory studies have suggested that interleukin-6 (IL-6) is related to COVID-19; however, no correlation between IL-6 and long COVID-19 is known. We designed a systematic review and meta-analysis to assess the relationship between IL-6 levels and long COVID-19. Methods: Databases were systematically searched for articles with data on lon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…In the context of viral respiratory infections, innate immune responses activate innate lymphocytic cells of a type‐2 phenotype (ILC‐2) which release a range of cytokines associated with allergic diseases 55 . This process has been observed in COVID‐19 patients and linked with more favourable outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of viral respiratory infections, innate immune responses activate innate lymphocytic cells of a type‐2 phenotype (ILC‐2) which release a range of cytokines associated with allergic diseases 55 . This process has been observed in COVID‐19 patients and linked with more favourable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Other immunological (dys) regulation processes are also suspected to influence the development of LC, e.g., Th-17 or cytokine activity, in particular interleukin (IL) 6 53,54. In a recent systematic review and meta-analysis of 16 studies, Yin et al even postulate that increased IL-6 levels might predict LC 55.…”
mentioning
confidence: 99%
“…In addition, there was an observed elevation in lymphocytes and IL-6 in these patients (Yong, Halim et al 2023). Yin et al (2023) also reported a significant increase in IL-6 levels in LC patients compared to healthy controls (Yin, Agbana et al 2023).…”
Section: Introductionmentioning
confidence: 96%
“…However, the two meta-analyses that examined immune functions in LC did not provide a comprehensive examination of the immune profiles, including the neurotoxicity profile (Yin, Agbana et al 2023, Yong, Halim et al 2023. Therefore, a more extensive examination of cytokines/chemokines/growth factor profiles in LC would be instrumental in elucidating the mechanisms of this illness.…”
Section: Introductionmentioning
confidence: 99%
“…6 Persistent inflammation, signposted by elevated blood concentrations of C-reactive protein and proinflammatory cytokines, has also been reported in people with long COVID. 7,8 The underlying causes of this inflammatory process nonetheless remain obscure. Dysregulation of the complement cascade has been implicated as a driver of inflammation in many diseases, including acute COVID-19.…”
Section: Introductionmentioning
confidence: 99%